THE EFFECTIVENESS OF BACK MASSAGE USING VIRGIN COCONUT OILAND WHITE PETROLEUM JELLY TO PREVENT PRESSURE SORES - Enna Rossalina Sihombing; Risma Yuniarlina; Sudibyo Supardi (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to prove the effectiveness of back massage using Virgin Coconut Oil (VCO)  and White Petroleum Jelly (WPJ) to the prevention of pressure sores in patients who are at risk in the Health Services St. Carolus, Jakarta. Methods: This research is quantitative research with posttest only quasi-experimental design. The study was conducted on May 2013. Study sample as many as 25 respondents got action back massage using VCO and 25 respondents get the action back massage using WPJ, sampling techniques with a simple random manner. Results: Results of analysis Chi - square and Fisher showed that back massage with VCO to prevent the occurrence of pressure sores was significantly (p = 0.025) and a back massage with WPJ can help prevent pressure sores were significantly (p = 0.005), so there is no difference keefektivitas between back massage using VCO and VCO in the prevention of pressure sores (p <0:05). Results of multivariate logistic regression showed that low blood protein levels 36 times the risk of incidence of pressure sores with p = 0.025 (α <0,05). Conclusion: The results suggest that using a back massage with VCO and WPJ in interventions to prevent pressure sores in patients who are at risk of pressure sores can be used; otherwise it will be considered a patient's blood protein levels.